Promoting Awareness about Pedagogical Content Knowledge - Ouerghi, Meissa; Kilani, Chiraz (Tauladan Fathimah Azzahra, 2023)
The purpose of this research is to evaluate the impact of the feedback gained from targeted self-confrontation on a teacher’s knowledge about his own practice. To do so, we opted for a case study within a qualitative approach. Through a sequence of self-confrontations, we employed content representation (CoRe) as a tool to advance a teacher’s pedagogical content awareness. We investigated the evolution of content representation during three self-confrontations assisted by CoRe. And we used the outcomes to draw up a CoRe design for each self-confrontation. The topic of teaching was air components and combustion. The results show an important increase of content aspects considered by the teacher during self-confrontation. We concluded that CoRe is an efficient tool that can contribute to elicit teacher’s awareness about the significant aspects of content pedagogical knowledge.